Remoção de óleo da água produzida de petróleo utilizando leitos coalescedores de fibra de coco e de fibra sintética - Dacal, Ruth Germaine Vrijdags (2017)
A major problem in the petrochemical industry is the substantial volume of produced water that is brought to the surface during oil and gas production operations. The water produced has a complex composition of organic and inorganic compounds that varies according to location, time of production and depth. The treatment of produced water is a subject of great importance due to legislation and environmental concerns. Inspection bodies regulate the disposal of this effluent from the content of oils and greases, where an appropriate treatment must be made to meet the limits of the norms. Bed coalescers can be an interesting option as they can separate tiny droplets of oil that are dispersed. The objective of the present work was to design and construct an experimental unit of a bed coalescer for the study of the treatment of synthetic produced water with steady state horizontal flow, varying parameters that affect efficiency such as: flow velocity, bed length and bed material. The coalescing beds used were synthetic fiber with abrasive mineral and dry coconut fiber, at flow rates of 8.7; 12.3; 15.9 and 25.9 m / h, corresponding to flow rates of 60, 85, 110 and 180 L / h, and bed lengths of 5, 10 and 15 cm. The porosity was kept constant at 0.944 in all assays. The synthetic emulsion to simulate the produced water was prepared in the laboratory using tap water, petroleum and the Sodium Lauryl Sulphate emulsifier with TOG of approximately 400 ppm. The effluent concentration, the separation efficiency and the pressure drop were analyzed. The separation efficiency using coconut fiber ranged from 40.3 to 96.7%, while the synthetic fiber ranged from 69.2 to 96.8%. In the coconut fiber bed it was possible to identify the critical velocities for each bed length and the optimal bed length was 10 cm. In the synthetic fiber, within the range of the analyzed parameters, all the tests performed resulted in near efficiencies, it was not possible to determine the optimum length. The results obtained demonstrate that the use of coalescing beds with these two materials can be an alternative for the treatment of the produced petroleum water for the purpose of disposal, reinjection or other purposes.